Figure 23 from: Prous M, Liston A, Mutanen M (2021) Revision of the West Palaearctic Euura bergmanni and oligospila groups (Hymenoptera, Tenthredinidae). In: Proshchalykin MYu, Gokhman VE (Eds) Hymenoptera studies through space and time: A collection of papers dedicated to the 75th anniversary of Arkady S. Lelej. Journal of Hymenoptera Research 84: 187-269. https://doi.org/10.3897/jhr.84.68637 - Prous, Marko; Liston, Andrew; Mutanen, Marko (Zenodo, 2021)
Figure 23 Euura brevivalvis larvae. A–D Finland 2019 Betula pubescensE DEI-GISHym83698 Sweden 2017 Betula nanaF DEI-GISHym83696 Sweden 2017 Betula nana.